Studi kualitatif pengalaman emosi ayah dalam pengasuhan anak balita - Fadhilah Khoirunnisa; Annisa Hasna Fadhilah; Zainal Abidin (Universitas Brawijaya, 2023)
The presence of a father in childcare is as important as a mother. This study aims to explore how fathers describe their emotional experiences of parenting. The research participants were fathers who have children under the age of five (1-3 years old). The data collection method used a semi-structured interview technique conducted online with reference to the Parent Development Interview-Revised (PDI-R). A phenomenological approach and iterative coding techniques were used to analyze the data and determine themes. The results identified six main emotions: joy, pain/difficulty, happiness, pride, annoyance/anger, and guilt based on four father’s experiences in parenting: father-child relationship, child-focused experience, father-focused experience, and father role fulfillment experience. The implication of this study is that people can know and realize that fathers feel a variety of positive and negative emotions in their relationship with children, so that they can comprehensively explore the role of fatherhood.